Promoting Disruptive Innovation in Open and Distance Learning Institutions in Nigeria - FALADE, Ayotunde Atanda; OGUNLADE, Oyeronke Olufunmilola; TAIWO, Simeon Ayoola (Ilorin Journal of Education, 2024)
The rapid development in emerging technologies has brought remarkable changes in the 21st century; their roles are becoming increasingly important in our educational system, especially in open and distance learning (ODL). ODL program is considered as one of the most important educational systems in Nigeria as it provides opportunities for those who could not afford to leave their jobs regardless of age or qualification. This paper is theoretical in nature; focuses on historical developments, benefits, mode and challenges of distance learning in Nigeria as well as on promoting the use of technologies such as disruptive in Nigeria’s ODL centres. The paper is theoretical; its methodology lies on reviewing of relevant literatures. The study revealed that in spite of potential advantages of ODL in Nigeria, the following challenges militated its sustenance; change in policy, epileptic power supply, cost, inadequate staff and attitudes. The study therefore recommended amongst many; stable policy, electric power supply, and positive attitude to global change in the use of new technology. In addition, the Nigerian Universities offering ODL courses should embrace promote and deploy the disruptive change and its technologies in Nigeria’s ODL centres to improve the quality of ODL program in Nigeria.